2020
DOI: 10.1177/1045389x20966057
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experiment of vibro-impact vibration energy harvester based on a partial interlayer-separated piezoelectric beam

Abstract: Piezoelectric-based energy harvesting techniques offer a promising way to transform vibration energy into electric energy. However, many vibration energy harvesters (VEH) can only work under narrow bandwidths and limited high frequencies to restrict their working performance. In this paper, a vibro-impact piezoelectric VEH is proposed, where a partial interlayer-separated piezoelectric beam is designed to improve the voltage output and frequency bandwidth of the VEH. First, the mechanism of the proposed VEH is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Wu et al (2014) designed a two-degree-of-freedom nonlinear harvester and demonstrated the proposed scheme can achieve wider bandwidth between two natural frequencies. Cao et al (2021) designed a vibro-impact piezoelectric energy harvester and obtained the broadband amplitude-frequency response curve of bimodal by using an approximate analytical method. Jiang et al (2022) explored a novel one-to-one internal resonance to scavenge flow energy from vortex-induced vibrations, the mechanism of synchronous oscillations was introduced by the amplitude-frequency relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2014) designed a two-degree-of-freedom nonlinear harvester and demonstrated the proposed scheme can achieve wider bandwidth between two natural frequencies. Cao et al (2021) designed a vibro-impact piezoelectric energy harvester and obtained the broadband amplitude-frequency response curve of bimodal by using an approximate analytical method. Jiang et al (2022) explored a novel one-to-one internal resonance to scavenge flow energy from vortex-induced vibrations, the mechanism of synchronous oscillations was introduced by the amplitude-frequency relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous technical applications use vibro-impact, including cutting and grinding equipment, pile-driving machines, turbomachinery, frequent rubbing of rotor blades and stators, and hand-held percussion devices [ 59 ]. Several studies investigated triboelectric and electrostatic effects utilizing vibro-impact structures and achieved higher bandwidth compared to the nonimpact harvesters [ 60 ]. The vibro-impact of multidegrees-of-freedom systems increased the operational bandwidth [ 51 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the effective ways to improve the output performance of PVEH is to match its operating frequency with the ambient frequency range. However, this general linear piezoelectric energy harvesting system is commonly limited to a narrow frequency bandwidth [9]- [11]. When facing the above dilemma, various performance enhancement techniques have been proposed and studied to help traditional PVEH achieve broadband bandwidth and improve energy harvesting efficiency, mainly including multimodal [12], [13], frequency tuning [14]- [16], frequency up conversion [17]- [20] and nonlinear techniques [21]- [25].…”
Section: Introductionmentioning
confidence: 99%